Neutron Scattering from Porous Materials and Confined Fluids: Applications to CO2 Sequestration and Oil Recovery - Stefanopoulos, Konstantinos Leonidas (HNPS Advances in Nuclear Physics, 2022)
In the current study we briefly review the advantages of utilising elastic neutron scattering techniques to reveal the structure of porous materials and pore-confined fluids. Furthermore, we highlight the benefits of utilising in situ CO2 injection and neutron scattering in model porous systems as well as in sedimentary rocks to explore the pore morphology, the pore accessibility and the structural properties of pore-confined CO2. This information is important for the design of optimal CO2 sequestration as well as gas and oil recovery projects.